Kaspar Hauser ou a fabricação da teoria - Dascal, Marcelo (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
In a recent book, Isidoro Blickstein has attempted to reanalyse the well-known case of Kaspar Hauser - the young man found in 'savage' condition, and later brought to and cared for in Nuremberg, where he died in mysterious circumstances. His main thesis is that this case shows that the acquisition of language (which Kaspar Hauser somewhat achieved in Nuremberg) os neither a necessarynor a sufficient condition for the development of other cognitive abilites (in which Kaspar Hauser remained deficiente). In particular, it argued that, in spite of acquiring language, K. H. 's ' decodification of the world's meaning (including his perceptual system and mental structures) remained aberrant. The conclusion is that both, such cognitive abilities and language, are conditioned by 'praxis', which generates the required 'social spectacles' through wich reality is 'manufactured', thereby acquiring 'meaning'. It was the lack of praxis, rather than the lack of langage - in the first place - that determined, therefore, K.H. 's permanent impairment and inability to cope with the new world he was exposed to. The thesis is appealing in itsekf, and is it is not directly questioned here; what is questioned is the claim that K.H. 's case provides support for such a thesis. This is done on both methodological and substantive grounds. In particular, it is shown that, due to the lack of evidence concerning this case, one cannot say with any degree of precision what precisely the phrase 'K.H. acquired language' refers to, nor, for that matter, in what consisted his alleged cognitive deficit. Thus, rather than estsblishing a particular position on the issue of the relationship between language and thought, this analysis of K.H. 's case only a further suggestive speculation about the possible nature of such a relationship.